Assessment of severity of Parkinson’s disease by optical coherence tomography - Bharat Vishnu Reddy Bindela; Vamsavardhana Reddy Pidathala; Kamalesh Tagadur Nataraju (Asian Journal of Medical Sciences, 2022)
Background: Parkinson’s disease (PD) is the second most common movement disorder after essential tremor. Diminished visual acuity, color vision, and contrast sensitivity are also described in PD. Optical coherence tomography (OCT), a producible test for axonal degeneration, helps in prognosticating diseases such as Alzheimer’s, Parkinson’s, and multiple sclerosis. Aims and Objectives: To assess the severity of Parkinson’s disease with the changes in various variables of OCT. The objective is to evaluate variables such as (RNFL, CMT, TMV) of both eyes with SD – OCT. Materials and Methods: It is a hospital-based cross-sectional study conducted for a period of 22 months at the department of neurology. A total of 55 PD patients and 30 age- and sex-matched controls were evaluated. Results: There was a significant difference between patients and controls in average retinal nerve fiber layer (RNFL) and all RNFL quadrants in both the eyes (P<0.001). A significant negative correlation was found between the RNFL thickness and Unified Parkinson’s Disease Rating Scale (UPDRS) motor score and Hoehn and Yahr (H&Y) score in both the eyes (P<0.001). A significant negative correlation was found between total macular volume (TMV) and central macular thickness (CMT) with UPDRS motor score in both the eyes (P<0.001). A significant negative correlation was found between CMT and H&Y stage in both the eyes (P<0.001). There was a significant difference between patients and controls in CMT and TMV in both the eyes (P<0.001). Conclusion: A significant negative correlation between severity and stage of the PD with OCT values was identified, which may suggest the possibility of dopaminergic depletion in the retina corresponding with basal ganglia dopamine depletion.